Noninvasive dynamic measurements of cerebral perfusion with frequency-domain near-infrared spectroscopy - Pham, Thao. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Sergio Fantini.; Committee: Irene Georgakoudi, Brian Tracey, and Blaise Frederick.; Keyword: Biomedical engineering.